2023
DOI: 10.3390/children10101693
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Metabolomic Signatures for Ischemic Hypoxic Encephalopathy Using a Neonatal Rat Model

Yulia Shevtsova,
Chupalav Eldarov,
Natalia Starodubtseva
et al.

Abstract: A study was performed to determine early metabolomic markers of ischemic hypoxic encephalopathy (HIE) using a Rice–Vannucci model for newborn rats. Dried blood spots from 7-day-old male and female rat pups, including 10 HIE-affected animals and 16 control animals, were analyzed by liquid chromatography coupled with mass spectrometry (HPLC-MS) in positive and negative ion recording modes. Multivariate statistical analysis revealed two distinct clusters of metabolites in both HPLC-MS modes. Subsequent univariate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…To simplify the multifactorial system in patients with HIE and to identify specific patterns of brain injury, proteomic and metabolomic analyses are used in in vivo and in vitro models. Using an ischemia-hypoxia model (carotid artery ligation and exposure to a mixed gas of 92% N2/8% O2 for 2 h), our recent study demonstrated the central role of glycerophospholipids, steroid biosynthesis, and fatty acid metabolism in triggering systemic responses in 7-day-old rats [21]. Other authors performed metabolomic studies of hypoxic-ischemic injury in neonatal pigs after hypoxia and 120 min of reoxygenation phase.…”
Section: Resultsmentioning
confidence: 92%
“…To simplify the multifactorial system in patients with HIE and to identify specific patterns of brain injury, proteomic and metabolomic analyses are used in in vivo and in vitro models. Using an ischemia-hypoxia model (carotid artery ligation and exposure to a mixed gas of 92% N2/8% O2 for 2 h), our recent study demonstrated the central role of glycerophospholipids, steroid biosynthesis, and fatty acid metabolism in triggering systemic responses in 7-day-old rats [21]. Other authors performed metabolomic studies of hypoxic-ischemic injury in neonatal pigs after hypoxia and 120 min of reoxygenation phase.…”
Section: Resultsmentioning
confidence: 92%